Allama Iqbal’s Stance on Contemporary Socialism - Mujahid, Muhammad Umer Farooq; Ghulam Mohiuddin (Experimental Student Experiences, 2024)
This study correlates the thoughts and stance used in his urdu and persian poetry by Dr. Allama Muhammad Iqbal, the philosopher and poet of East, to the modern socialism. A total of 53 papers fulfilled the requirements to be eligible for the study per the PRISMA guidelines; however, 29 were disqualified, leaving a final count of 24 publications to be included in the investigation. Therefore, he established his thoughts on self-hood philosophy to revive dead authority and weaken self-awareness of the oriental. On the other hand, Iqbal does not connive the society at all. However, he receives that as an undeniable fact and intends to make a significant connection between the individual and society, although he prefers the individuality states to society. In reality, individuals' duties and rules are determined by the community. Individuals' respect and esteem are contingent on their compliance with and adoption of these duties and rules. Implementing the ideal human in Iqbal's perspective is via three steps: compliance with Divine Law, complete self-control and Divine vice regency. Muslim scholars have abandoned ijtihad, which bound the Muslim Ummah. Iqbal urged Muslims to restore the underlying power that derailed Muslim social thought. Iqbal's ideology was action-oriented and motivated by the Quranic concept in the declaration.